Apremilast interferes with the TGFβ1-induced transition of human skin fibroblasts into profibrotic myofibroblasts: in vitro study. (28th July 2020) - Cutolo, Maurizio; Soldano, Stefano; Montagna, Paola; Martinelli, Giulia; Tardito, Samuele; Corallo, Claudio; Giordano, Nicola; Tavilla, Pierpaolo; Cozzani, Emanuele; Parodi, Aurora; Sulli, Alberto; Pizzorni, Carmen; et al.
Abstract: Objectives: Fibroblast-to-myofibroblast transition and extracellular matrix overproduction represent progressive events in chronic inflammatory and fibrotic diseases, in which TGFβ1 is one of the key mediators. Phosphodiesterase 4 (PDE4) acts as a proinflammatory enzyme through the degradation of cyclic adenosine monophosphate and it is overexpressed in skin fibroblasts. The study investigated how apremilast (a PDE4 inhibitor) interferes with the intracellular signalling pathways responsible for the TGFβ1-induced fibroblast-to-myofibroblast transition and profibrotic extracellular matrix protein synthesis. Methods: Cultured human skin fibroblasts were stimulated with TGFβ1 (10 ng/ml) alone or combined with apremilast (1 and 10 μM) for 4, 16 and 24 h. Other aliquots of the same cells were previously stimulated with TGFβ1 and then treated with apremilast (1 and 10 μM) for 4, 16 and 24 h, always under stimulation with TGFβ1. Gene and protein expression of αSMA, type I collagen (COL1) and fibronectin were evaluated, together with the activation of small mothers against decapentaplegic 2 and 3 (Smad2/3) and extracellular signal-regulated kinase (Erk1/2) proteins. Results: Apremilast reduced the TGFβ1-induced increase in αSMA, COL1 and fibronectin gene expression at 4 and 16 h, and protein synthesis at 24 h of treatment in cultured fibroblasts, even for cells already differentiated into myofibroblasts by way of a previous stimulation with TGFβ1. Apremilast inhibited the TGFβ1-induced Smad2/3 and Erk1/2 phosphorylation at 15 and 30 min. Conclusion: Apremilast seems to inhibit in vitro the fibroblast-to-myofibroblast transition and the profibrotic activity induced by TGFβ1 in cultured human skin fibroblasts by downregulating Smad2/3 and Erk1/2 intracellular signalling pathways.